Analysis Of Factors Associated With Occupational Fatigue Among Motorcycle Workshop Workers In Jambi City, 2026 - Niki Rosalina Harianja; Hendra Dermawan Sitanggang; Usi Lanita; Willia Novita Eka Rini; Muldiasman Muldiasman (CV. AFDIFAL MAJU BERKAH, 2026)
Occupational fatigue is a common occupational health problem that may reduce productivity and increase the risk of workplace accidents, particularly among motorcycle workshop workers who are exposed to physically demanding tasks and unfavorable working conditions. This study aimed to analyze factors associated with occupational fatigue among motorcycle workshop workers in Jambi City. A quantitative cross-sectional study was conducted involving 46 workers selected using simple random sampling. Data were collected through questionnaires, observation, anthropometric measurements, and the Industrial Fatigue Research Committee (IFRC) Subjective Self-Rating Test. Data were analyzed using univariate and Chi-square analyses at a 95% confidence level. The results showed that 58.7% of respondents experienced occupational fatigue. Age, length of service, smoking habits, and work environment were significantly associated with occupational fatigue, with age demonstrating the strongest association. These findings indicate that both individual and workplace factors contribute to occupational fatigue. Improving workplace conditions and strengthening occupational health promotion programs are recommended to reduce fatigue and enhance workers' health, safety, and productivity.